2014
DOI: 10.14738/abr.24.379
|View full text |Cite
|
Sign up to set email alerts
|

Multivariables Determining Earnings per Share within the U.S. Medical Laboratories & Research Industry

Abstract: The* objective* of* this* study* is* to* examine* the* key* variables* determining* earnings*per*share*for*the*Research*Industry.*In*this*study*financial*statements* for*ten*years*(from*2003*to*2012)*of*the*publicly*listed*leading*U.S.*companies* in* the* Medical* Laboratories* and* Research* Industry* based* on* their* size* are* gathered.*In*making*proper*decisions,*we*need*to*take*into*consideration*such* indicators* as* financial* ratios,* operating* cash* flows,* and* firm* size.* Since* all* of* these* f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This research uses ten variables and each variable uses the measurement as presented in Table 1. Martani (2009), Taani (2011), Pouraghajan et al (2013), and Vedd et al (2014).…”
Section: This Research Uses Ten Variables and Each Variable Has Its Own Operational Definitionmentioning
confidence: 98%
“…This research uses ten variables and each variable uses the measurement as presented in Table 1. Martani (2009), Taani (2011), Pouraghajan et al (2013), and Vedd et al (2014).…”
Section: This Research Uses Ten Variables and Each Variable Has Its Own Operational Definitionmentioning
confidence: 98%
“…Profit accounting measurements: The net profit is considered an important tool that represents the value of the financial profits achieved by the companies during this period (Abdelghany, 2005).These profits have no relation to the company's available cash , but expresses the difference between the company's net sales and expenses according to the principle of revenue versus expenses based on an accrual basis (Khalayleh, 2004), and the profit is considered the main aim of any company moreover the aim of maximizing the profit is considered the most important indicator used to measure the efficiency of the management and its ability to make profits from the funds invested in the assets (Ali, 2003), as well as it reflects the profitability of any company and its policies and the decisions it follows (Vedd et al, 2014). It's also very useful to consider the net profit achieved a source of fund such as using them in the course of the study of the flow of funds in the company (Pouraghajan et al, 2013), these companies work to achieve their goal of profit making through these 2 decisions: a.…”
Section: Literature Reviewmentioning
confidence: 99%
“… The return on investment (ROI): This measures the amount of return achieved by the company when it uses a specific amount of funds in a specific amount of time and it is regarded as an indicator to measure the company's profitability in general, and this is the return on investment  The return on the shareholders equity (ROE): This measures the ability of the management to increase the investors return and whenever this index increases, the situation in the company improves, and (Vedd et al, 2014) study showed the importance of the (ROE) in affecting the profitability of the share as it is one of the most important equity tools.…”
Section: The Profitability Of the Funds Investedmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources: Research variables based on aforementioned reseraches byMartani (2009), Taani (2011),Pouraghajan et al (2013), andVedd et al (2014).…”
mentioning
confidence: 99%